ASME 2007 International Manufacturing Science and Engineering Conference 2007
DOI: 10.1115/msec2007-31060
|View full text |Cite
|
Sign up to set email alerts
|

Some Investigations Into Multi-Objective Optimization of Wire Electro-Discharge Machining of Al/SiCp Composites

Abstract: Non-traditional process like wire electro-discharge machining (WEDM) is found to show a promise for machining metal matrix composites (MMCs). However, the machining information for the difficult-to-machine particle-reinforced material is inadequate. This paper is focused on experimental investigation to examine the effect of electrical as well as non-electrical machining parameters on performance in wire electro-discharge machining of metal matrix composites (Al/SiCp). Taguchi orthogonal arrays were employed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The variation of MRR and surface roughness with machining parameters is mathematically modeled by using non-linear regression analysis method. Patil and Brahmankar [54] examined the effect of various input parameters such as pulse on time, pulse off time, ignition pulse current, wire speed, wire tension and flushing pressure on cutting speed and surface finish of Al/SiCp by using Taguchi methods. Shandilya et al [38] concluded that to achieve higher value of the average cutting speed, lower value of voltage and higher value of pulse-off time should be used during WEDC of SiCp/6061 Al MMC.…”
Section: Literature Review: Process Modeling and Optimizationmentioning
confidence: 99%
“…The variation of MRR and surface roughness with machining parameters is mathematically modeled by using non-linear regression analysis method. Patil and Brahmankar [54] examined the effect of various input parameters such as pulse on time, pulse off time, ignition pulse current, wire speed, wire tension and flushing pressure on cutting speed and surface finish of Al/SiCp by using Taguchi methods. Shandilya et al [38] concluded that to achieve higher value of the average cutting speed, lower value of voltage and higher value of pulse-off time should be used during WEDC of SiCp/6061 Al MMC.…”
Section: Literature Review: Process Modeling and Optimizationmentioning
confidence: 99%
“…However, wire breakages can be reduced by employing higher flushing pressures, higher pulse off times, and suitable values of servo reference voltage. In general, it was suggested that large pulse on time, high flushing pressure, appropriate wire speed and wire tension, large pulse off time, and appropriate pulse current should be used to obtain optimum machining performance [267]. Figure 27 displays the effect of discharge energy on SR and MRR during the WEDM of 45% (volume fraction) SiC p /Al [268].…”
Section: Wire Edm (Wedm)mentioning
confidence: 99%
“…Taguchi orthogonal array is one such approach which was used to study the effect of various input parameters such as current, pulse on-time, off-time, servo reference voltage, maximum feed speed, wire speed, flushing pressure and wire tension on kerf width and cutting speed. [6] The Taguchi analysis, being used for single objective analysis, has been improved for multi objective optimization with the use of Grey relational approach along with Taguchi orthogonal array [7].…”
Section: Introductionmentioning
confidence: 99%